2012
DOI: 10.1088/1742-6596/372/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Continuum reverberation mapping in az= 1.41 radio-loud quasar

Abstract: Q0957+561 was the first discovered gravitationally lensed quasar. The mirage shows two images of a radio-loud quasar at redshift z = 1.41. The time lag between these two images is well established around one year. We detected a very prominent variation in the optical brightness of Q0957+561A at the beginning of 2009, which allowed us to predict the presence of significant intrinsic variations in multi-wavelength light curves of Q0957+561B over the first semester of 2010. To study the predicted brightness fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…On the other hand, mass accretion fluctuations propagate from outer to inner radii in the accretion disc, which means that the flux variations caused by the mass accretion fluctuations occur at the optical (longer) wavelengths prior to the UV (shorter) wavelengths (e.g., Arévalo et al 2008;Uttley & Casella 2014). Within the UV-optical wavelength range, the inter-band time delay of the AGN continuum for several AGNs are reported to be as expected in the reprocessing model (e.g., Collier et al 1999;Sergeev et al 2005;Suganuma et al 2006;Czerny & Janiuk 2007;Cackett, Horne & Winkler 2007;Goicoechea et al 2012;Chelouche 2013;Lohfink et al 2014;Shappee et al 2014;McHardy et al 2014;Edelson et al 2015), although results from different observing campaigns are conflicting (see, e.g., Nandra et al 1998;Uttley 2006). Moreover, several authors have pointed out that the X-ray luminosity of AGNs is insufficient to power the large UV-optical variability amplitude (e.g., Antonucci et al 1996;Gaskell 2008;Edelson et al 2014;Uttley & Casella 2014).…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, mass accretion fluctuations propagate from outer to inner radii in the accretion disc, which means that the flux variations caused by the mass accretion fluctuations occur at the optical (longer) wavelengths prior to the UV (shorter) wavelengths (e.g., Arévalo et al 2008;Uttley & Casella 2014). Within the UV-optical wavelength range, the inter-band time delay of the AGN continuum for several AGNs are reported to be as expected in the reprocessing model (e.g., Collier et al 1999;Sergeev et al 2005;Suganuma et al 2006;Czerny & Janiuk 2007;Cackett, Horne & Winkler 2007;Goicoechea et al 2012;Chelouche 2013;Lohfink et al 2014;Shappee et al 2014;McHardy et al 2014;Edelson et al 2015), although results from different observing campaigns are conflicting (see, e.g., Nandra et al 1998;Uttley 2006). Moreover, several authors have pointed out that the X-ray luminosity of AGNs is insufficient to power the large UV-optical variability amplitude (e.g., Antonucci et al 1996;Gaskell 2008;Edelson et al 2014;Uttley & Casella 2014).…”
Section: Discussionmentioning
confidence: 75%
“…The future constraints on size of sources will be compared to current results from microlensing analyses (e.g. Refsdal et al 2000;Hainline et al 2012) and reverberation mapping techniques Goicoechea et al 2012). The main results from LT polarimetric observations are presented in Table 7.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…There is also strong evidence supporting the presence of a centrally irradiated AD in the heart of QSO B0957+561. A Chandra-UVOT-LT monitoring campaign from late 2009 to mid-2010 suggested that a central EUV source drives the variability of the first GLQ, so EUV flares originated in the immediate vicinity of the black hole are thermally reprocessed in the AD at 20−30 Schwarzschild radii from the dark object 10 (Gil-Merino et al 2012;Goicoechea et al 2012). Interpreting the reverberationbased size of the 2600 Å source as a flux-weighted emitting radius (e.g.…”
Section: Quasar Accretion Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kochanek 2004;Eigenbrod et al 2008;Poindexter, Morgan & Kochanek 2008;Dai et al 2010;Morgan et al 2010Morgan et al , 2012Hainline et al 2013;Mosquera et al 2013;Blackburne et al 2014;MacLeod et al 2015). Multiwavelength intrinsic variability of GLQ images also produces valuable reverberation maps of emitting regions of quasars (Gil-Merino et al 2012;Goicoechea et al 2012), which will become in critical tools to check microlensing-derived source structures.…”
Section: Introductionmentioning
confidence: 99%